Physical activity in individuals with spinal cord injury: Exercise and technologies for health promotion / Nazirah Hasnan - Nazirah Hasnan, Abdullah (2015)
Spinal cord injury (SCI) adversely affects the physiological functions of most organ systems resulting in restrictions in performance of daily activities and social participation. Depending on the level of injury, SCI individuals can be amongst the most physically deconditioned of individuals with a disability. SCI renders profound effects on fitness, exercise capacities and health. There is increased risk of developing secondary health conditions such as cardiovascular disease and diabetes in chronic SCI survivors. There is good evidence that exercise is effective for improving physical fitness and general health in the SCI population. Leg exercise is usually restricted because of paralysis after SCI and upper body exercise is not as beneficial as lower body exercise due to the relatively small muscle mass in the arms. Technological advancements have allowed functional electrical stimulation (FES) muscle contractions to enable exercise for the paralysed lower limbs of persons with SCI. Other technologies including virtual reality (VR) approaches have also begun to be deployed as exercise and rehabilitation strategies in recent years. This thesis comprised of three studies, which examined exercise outcomes involving the use of assistive technologies (FES and VR) for exercise testing and training in persons with SCI. The acute physiological response of FES-assisted cycling exercise was first assessed comparing the different exercise modalities that were available for people with SCI. These vii were arm crank ergometry (ACE), FES–leg cycle ergometry (FES-LCE), ACE+FES-LCE and an integrated arm and FES-leg tricycle. It was found that combined arm and leg (hybrid) FES cycling exercise could develop higher oxygen uptake and cardiovascular demand compared to ACE or FES-LCE alone. Hybrid FES cycling evoked up to 148% higher oxygen uptake, 49% greater cardiac output and 47% higher heart rate than FES-LCE during steady-state exercise thereby concluding that FES-LCE by itself was insufficient to promote aerobic fitness and training benefit in people with SCI. Based on the findings of the first experiment, the acute physiological and psychological responses to hybrid FES cycling were then further assessed in different exercise environment i.e. natural outdoor and simulated VR-enhanced indoor environment. With only 5% and 1% difference in the cardiorespiratory and perceptual-psychological responses respectively between the two modes, it was concluded that indoor and outdoor modes have similar exercise “dose-potency” and self-perceived effort. Following these experiments on acute responses, a final study which examined the fitness, carbohydrate and lipid metabolisms and psychological outcomes following a 6-week high intensity interval training employing hybrid FES cycling training was carried out. The study demonstrated greater aerobic fitness by 16% and increased muscle mass by 6%. The 6-week training resulted in 60-80% improvement in negative mood states and up to 76% increase in post-exercise positive feeling states. However there was a lack of change in their lipid profile and glucose metabolism. viii The importance of incorporating regular physical activity and exercise into the lifestyle of people with SCI is evident. The studies conducted herein identified the best exercise modality; propose strategies for enhancement of exercise participation and highlight the benefits of exercise in this population.